Understanding gut microbial diversity using systems based on the Constrained-Disorder Principle provides a novel approach to targeting gut microbiome therapies - Perzon, Ofer; Ilan, Yaron (Frontiers in Microbiology, 2025)
Background/aimsThe diverse composition of the gut microbiome is vital for human health, influencing digestion, immune regulation, and disease resistance. While higher diversity is generally associated with resilience, reduced and excessive diversity can lead to health issues.MethodsThis paper introduces the Constrained Disorder Principle (CDP) as a new framework for understanding microbial diversity.ResultsThe CDP emphasizes the significance of maintaining variability within certain boundaries to sustain ecosystem stability and promote health. It considers intra- and inter-individual variability, illustrating how microbial ecosystems adapt throughout different life stages, genetic backgrounds, and environmental exposures. Integrating CDP-based artificial intelligence systems may enable the establishment of personalized diversity thresholds, predict dysbiosis, and refine interventions such as probiotics, prebiotics, fecal microbiota transplantation, and customized dietary strategies. CDP-driven platforms enhance therapeutic precision by utilizing variability induction, feedback loops, and microbial signature analysis to optimize diversity goals and identify actionable biomarkers.ConclusionThis platform can pave the way for adaptive, individualized disease prevention and treatment strategies, bridging the gap between microbial ecology and precision medicine. It provides a powerful tool for harnessing the therapeutic potential of gut microbial diversity to enhance human health.